Impact of the ABO and RhD Blood Groups on the Evaluation of the Erythroprotective Potential of Fucoxanthin, β-Carotene, Gallic Acid, Quercetin and Ascorbic Acid as Therapeutic Agents against Oxidative Stress - Ricardo Iván González-Vega; Miguel Ángel Robles-García; Litzy Yadira Mendoza-Urizabel; Kelly Nabil Cárdenas-Enríquez; Saúl Ruiz-Cruz; Melesio Gutiérrez-Lomelí; Rey David Iturralde-García; María Guadalupe Avila-Novoa; Fridha Viridiana Villalpando-Vargas; Carmen Lizette Del- (MDPI AG, 2023)
Previous studies detail that different blood groups are associated with incidence of oxidative stress-related diseases such as certain carcinomas. Bioactive compounds represent an alternative for preventing this oxidative stress. The aim of this study was to elucidate the impact of blood groups on the erythroprotective potential of fucoxanthin, β-Carotene, gallic acid, quercetin and ascorbic acid as therapeutic agents against oxidative stress. The impact of ABO blood groups on the erythroprotective potential was evaluated via the antioxidant capacity, blood biocompatibility, blood susceptibility and erythroprotective potential (membrane stabilization, in vitro photostability and antihemolytic activity). All tested antioxidants exhibited a high antioxidant capacity and presented the ability to inhibit ROO•-induced oxidative stress without compromising the cell membrane, providing erythroprotective effects dependent on the blood group, effects that increased in the presence of antigen A. These results are very important, since it has been documented that antigen A is associated with breast and skin cancer. These results revealed a probable relationship between different erythrocyte antigens with erythroprotective potential, highlighting the importance of bio-targeted drugs for groups most susceptible to certain chronic-degenerative pathologies. These compounds could be applied as additive, nutraceutical or encapsulated to improve their bioaccessibility.